Stress manifestations as reflected by serum biochemistry at women's volleyball Penicilina Iasi Team (2011 - 2012 competitive season, A1 Division) - Puni,A. R.; Rata, G. (Procedia - Social and Behavioral Sciences, 2014)
Our present study belongs to a broader research project, targeting the training optimization in performance volleyball through stress control, based upon Women's A1 Division Penicilina Iasi volleyball team, during the 2011-2012 season (in Romania). With the present proposal, we aim at discussing the levels of competitive stress, as revealed by serum biochemistry when analyzing the levels of glycaemia, serum urea and cholesterol. The participants in our research, namely ten athletes playing for Penicilina Iasi volleyball team, were the subject of DDFAO lab tests. The measurements were made during three key- moments of the competitive season: after the holydays, after returning from the mountain training camp, and right before the most important game in the championship (the last chance to avoid relegation). The research was based on two working hypothesis: 1. during different stages of the competitive season, players` stress levels vary; 2. stress levels could be improved through specific mental and physical training methods. The final results confirmed our initial assumptions.